Assessment as Learning dalam Evaluasi Reflektif Pembelajaran Qirā’ah di Madrasah Ibtidaiyah - Nurhaliza, Tria Novia; Syihabuddin, Syihabuddin; Maulani, Hikmah (Aphorisme: Journal of Arabic Language, Literature, and Education, 2025)
This study explores the implementation of assessment as learning through reflective evaluation in Arabic reading (qirā’ah) instruction for fifth-grade students at Islamic elementary schools. The research aims to examine how reflective assessment fosters students’ awareness of their own learning processes and contributes to the development of metacognitive reading skills. Using a descriptive qualitative design with a phenomenological approach, data were collected from fifteen purposively selected students through classroom observations, evaluative judgment, and reflective questionnaires. The data were analyzed thematically to identify reflective patterns in students’ responses. The findings indicate that students began to demonstrate reflective awareness in reading, particularly in self-assessment, managing personal biases, and seeking opportunities for feedback. However, challenges remain in discerning text quality and evaluating digital sources. The study contributes a novel perspective on reflective learning in Arabic education by positioning students as active participants in the assessment process. It suggests that assessment as learning can transform Arabic reading instruction into a more participatory, reflective, and lifelong learning-oriented practice.